2013
DOI: 10.4028/www.scientific.net/amr.831.253
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Adsorbent with Lead Removal Ability Using Sulfur-Impregnation

Abstract: Preparation of the adsorbent with lead removal ability using a sulfur impregnation was studied. Coal, palm shell, waste tire and diatomite, were used as raw materials. Raw material was mixed with K2S powder and then heated at 800 °C or 900 °C for 30 min in nitrogen to produce a sulfur-impregnated adsorbent. The sulfur-impregnated adsorbents prepared from coal, palm shell, waste tire and diatomite at 800 °C have lead removal property, and the order of lead removal ability is the adsorbent from coal = palm shell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that adsorbents with sulfur group are effective for removing heavy metal ions from aqueous solution because heavy metals have a high affinity for the group of sulfur due to the Pearson's rule 14,15) . There are several methods for preparing a sulfurized adsorbent, for example, using a solution containing sulfur such as CS 2 16,17) , DMDS 18) , Na 2 S 19,20) , K 2 S [21][22][23][24] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that adsorbents with sulfur group are effective for removing heavy metal ions from aqueous solution because heavy metals have a high affinity for the group of sulfur due to the Pearson's rule 14,15) . There are several methods for preparing a sulfurized adsorbent, for example, using a solution containing sulfur such as CS 2 16,17) , DMDS 18) , Na 2 S 19,20) , K 2 S [21][22][23][24] and so on.…”
Section: Introductionmentioning
confidence: 99%